Improving the high-cycle fatigue strength of heterogeneous carbon nanotube/Al-Cu-Mg composites through grain size design in ductile-zones. (1st October 2021) - Ma, K.; Li, X.N.; Liu, K.; Chen, X.G.; Liu, Z.Y.; Xiao, B.L.; Ma, Z.Y.
Abstract: Heterogeneous structure consisting of brittle-zones (BZs) rich of carbon nanotubes (CNTs) and ductile-zones (DZs) free of CNTs, was an effective way to improve the strength-ductility of CNT reinforced Al (CNT/Al) composites. Two heterogeneous CNT/2009Al composites with coarse grain (CG, 2 μm) DZs or ultra-fine grain (UFG, 500 nm) DZs were fabricated and achieved enhanced strength-ductility. However, the heterogeneous composite with CG DZs had a lower high-cycle fatigue strength as well as fatigue strength/tensile strength ratio than the uniform composite, while the heterogeneous composite with UFG DZs exhibited the increased fatigue strength and the same level of fatigue strength/tensile strength ratio compared to the uniform composite. It was found that the improved fatigue properties for the heterogeneous composite with the UFG DZs could attribute to two reasons. Firstly, the UFG for the DZs significantly increased the strength of DZs, which effectively reduced the strain localization in the DZs. Secondly, the dislocations piling up at the grain boundaries of the BZs, as well as the stress concentration at the boundaries between the DZs and BZs were relieved due to the coordinated micro-strain for the heterogeneous structure. This provided a simple strategy for the structural design of heterogeneous composites with high fatigue strength. Graphical abstract: Image 1